RNA N6-Methyladenosine Responds to Low-Temperature Stress in Tomato Anthers - Yang, Dandan; Xu, Huachao; Liu, Yue; Li, Mengzhuo; Ali, Muhammad; Xu, Xiangyang; Lu, Gang (Frontiers in Plant Science, 2021)
Cold stress is a serious threat to subtropical crop pollen development and induces yield decline. N6-methyladenosine (m6A) is the most frequent mRNA modification and plays multiple physiological functions in plant development. However, whether m6A regulates pollen development is unclear, and its putative role in cold stress response remains unknown. Here, we observed that moderate low-temperature (MLT) stress induced pollen abortion in tomato. This phenotype was caused by disruption of tapetum development and pollen exine formation, accompanied by reduced m6A levels in tomato anther. Analysis of m6A-seq data revealed decreased enrichment in 1805 transcripts and increased enrichment in 978 transcripts in MLT-stressed anthers compared with those in anthers under normal temperature. These differentially m6A enriched transcripts under MLT stress were mainly related to lipid metabolic process, adenosine triphosphatase (ATPase) activity, and ATP-binding pathways. An ATP-binding transcript, SlABCG31, had significantly up-regulated m6A modification levels, which was inversely correlated dramatically down-regulated expression level. These changes correlated with higher abscisic acid levels in anthers and disrupted pollen wall formation under low-temperature stress. Our findings characterized m6A as a novel layer of complexity in gene expression regulation under low-temperature conditions during tomato pollen development.